Mechanisms of Zhixiao Tang on Anti-Inflammatory Multiple Targets and Multiple Components: Metabonomics Combined with Database Mining Technology - Zhang K; Li C; Wu P; Gao X; Feng X; Shen J; Zhang N; Hu X; Wang S; Zhang H; Lv J; Sun J (Dove Medical Press, 2024)
Kaiyue Zhang, Chunnan Li, Peitong Wu, Xiaochen Gao, Xueqin Feng, Jiaming Shen, Nanxi Zhang, Xuesheng Hu, Shuo Wang, Hui Zhang, Jingwei Lv, Jiaming Sun Jilin Ginseng Academy, Changchun University of Chinese Medicine, Changchun, Jilin, People's Republic of ChinaCorrespondence: Jiaming Sun; Jingwei Lv, Changchun University of Chinese Medicine, No. 1035, Boshuo Road, Nanguan District, Changchun, 130117, People's Republic of China, Tel +0431-86763809, Fax + 8676 3968, Email Sun_jiaming2000@163.com; jingwei-lv@hotmail.comPurpose: Zhixiao Tang (ZXT), a traditional Chinese compound prescription, has been used clinically to treat pneumonia in China. However, the underlying mechanism of ZXT treatment in pneumonia is still unclear. The present study aimed to reveal the potential mechanism of ZXT in pneumonia using a strategy combining metabolomics and network pharmacology.Methods: Initially, the chemical compositions were identified by UPLC-QE-Orbitrap-MS, while the prediction of potential signal pathways was performed through network pharmacology. To assess the anti-inflammatory properties of ZXT in the context of pneumonia, models of 16HBE cells induced by LPS and zebrafish induced by CuSO4 were established to measure levels of inflammatory markers and apoptosis. Subsequently, the differential changes of endogenous metabolites in cells caused by ZXT were examined using metabolomics technology, and the molecular docking analysis of key targets was carried out using Autodock Vina software. Ultimately, the validation of the primary pathways and targets was conducted through quantitative RT-PCR and Western blot techniques.Results: A total of 75 compounds were identified through UPLC-QE-Orbitrap-MS analyses. Network pharmacological analysis shows that it plays an anti-inflammatory role in C-type lectin receptor signaling pathway. After ZXT intervention, the inflammatory factors and apoptosis in cells were significantly reduced. Metabonomics analysis showed that 18 metabolites changed significantly. Four key genes were identified, which exhibited partial compatibility with the findings of network pharmacology. Molecular docking analysis confirmed the substantial affinity of the primary targets for ZXT. Furthermore, ZXT exerted a suppressive effect on neutrophil migration, down-regulated the expression of pro-inflammatory cytokine genes, and inhibited the up-regulation of the Dectin-1/SYK/NF-κB signaling pathway. In vivo cell experiments also yielded consistent experimental outcomes.Conclusion: This study enhances comprehension of the pharmacological mechanism underlying ZXT's efficacy in pneumonia treatment, thereby establishing a scholarly basis for future research and clinical utilization of ZXT in pneumonia management. Keywords: Zhixiao Tang, pneumonia, network pharmacology, integrated metabolomics, 16HBE, Zebrafish